The Flaws in Modern Monetary Theory (MMT) - Carneiro, Ricardo (Brazilian Keynesian Review, 2021)
The unusual rise of MMT in recent years, particularly after the 2008 global financial crisis, has made it an imperative issue, both from an academic point of view and in the debate on alternative economic policies. Departing from these facts, this article, without pretending to be exhaustive, aspires to carry out a critical evaluation of its main aspects. Namely (i) its understanding of money, and (ii) its proposal of economic policy, precisely its particular proposal to finance the public sector and to keep the economy in permanent full employment. The article does not seek to make an exegesis of its conceptions, nor does it carry out exhaustive analyzes of one of its aspects, but above all, starting from little controversial syntheses intends to examine the possible consequences of its economic policy proposals.